Martin Bucer and sixteenth century Europe: volume 2 - Krieger, Christian (Studies in medieval and reformation traditions, 1993)
This two-volume work describes the significant activities of Martin Bucer, reformer in Strasbourg, and the profound influence he exerted on his contemporaries. The collection brings together sixty contributions in English, German and French by leading Bucer and sixteenth century scholars. They highlight Bucer's profile and style, his theology, his attitude towards social questions of his time, his work in the church, his relationships with contemporaries in the city of Strasbourg and all over Europe, his position on contemporary issues and how his peers perceived him — in short, the many facets of thought, actions, and influence of an important but largely neglected sixteenth century reformer. They also provide new insight into the victories and defeats of Protestantism, and on Bucer's role in the progress of the Reformation in Europe. Dieses Buch stellt das Wirken und die vielfältigen Beziehungen des Strassburger Reformators Martin Bucer dar. Sechzig Beiträge prominenter Spezialisten Bucers und des 16. Jahrhunderts sind in den zwei Bänden vereint. Behandelt werden Bucers Profil und Stil, seine Theologie, seine Haltung zu gesellschaftlichen Fragen seiner Zeit, sein Wirken in der Kirche, seine Beziehungen zu Zeitgenossen in Strassburg und in ganz Europa, seine Verhältnis zu zeitgenössischen Strömungen, die Rezeption Bucers. Die verschiedenen Beiträge erhellen auf vielfältige Weise das Denken, das Wirken und die Austrahlung eines der grossen aber weithin vergessenen Reformators des 16. Jahrhunderts. Sie werfen auch ein neues Licht auf die Siege und Niederlagen der evangelischen Bewegung und die Rolle Bucers bei der Durchführung der Reformation in Europa. The print edition is available as a set of two volumes (9789004098862)